2010
DOI: 10.1051/0004-6361/201014077
|View full text |Cite
|
Sign up to set email alerts
|

Thermalisation and hard X-ray bremsstrahlung efficiency of self-interacting solar flare fast electrons

Abstract: Context. Most theoretical descriptions of the production of solar flare bremsstrahlung radiation assume the collision of dilute accelerated particles with a cold, dense target plasma, neglecting interactions of the fast particles with each other. This is inadequate for situations where collisions with this background plasma are not completely dominant, as may be the case in, for example, low-density coronal sources. Aims. We aim to formulate a model of a self-interacting, entirely fast electron population in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…A larger value of κ indicates that the spectrum is closer to Maxwellian. In fact, Galloway et al (2010) showed that the non-thermal, high-energy tail of a κ-like distribution can be thermalized into a Maxwellian over a timescale of 100 -1000 τ coll , where τ coll is the electron-electron collision time of the core particles and it can be ∼0.1s in a plasma with 30 MK temperature and 10 9 cm −3 density. Thus, it was speculated that, while electron acceleration may be achieved primarily by collisionless magnetic reconnection, the above-the-looptop source density determines the electron energy partition and the associated spectral slope of the source spectra.…”
Section: Event-to-event Variations Of the Non-thermal Tailmentioning
confidence: 99%
“…A larger value of κ indicates that the spectrum is closer to Maxwellian. In fact, Galloway et al (2010) showed that the non-thermal, high-energy tail of a κ-like distribution can be thermalized into a Maxwellian over a timescale of 100 -1000 τ coll , where τ coll is the electron-electron collision time of the core particles and it can be ∼0.1s in a plasma with 30 MK temperature and 10 9 cm −3 density. Thus, it was speculated that, while electron acceleration may be achieved primarily by collisionless magnetic reconnection, the above-the-looptop source density determines the electron energy partition and the associated spectral slope of the source spectra.…”
Section: Event-to-event Variations Of the Non-thermal Tailmentioning
confidence: 99%
“…This means that the progressively higher-E electrons are more difficult to equilibrate. In fact, the high-energy tail can take hundreds or thousands times longer to equilibrate than the thermal core of the distribution (Galloway et al 2010).…”
Section: Introductionmentioning
confidence: 99%